2014
DOI: 10.1007/s12032-014-0109-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of peripheral blood cells: new insights into Ewing sarcoma biology and clinical applications

Abstract: Ewing sarcoma (ES) is a group of highly aggressive small round cell tumors of bone or soft tissue with high metastatic potential and low cure rate. ES tumors are associated with a rapid osteolysis and necrosis. The currently accepted clinical prognostic parameters do not accurately predict survival of high-risk patients. Moreover, neither the subtype of EWS–FLI1/ERG in the tumor, nor the detection of fusion transcripts in the peripheral blood (PB) samples, has prognostic value in ES patients. We evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…42 Tumor-associated macrophages are known to promote cancer cell proliferation, immunosuppression and angiogenesis supporting metastasis and progression and through differentiation to M2 type macrophages expressing anti-inflammatory cytokines (IL-10, TGFβ) that have an inhibitory effect on cytotoxic CD8 + T cells. 43 Interestingly, in the peripheral blood monocytosis and other changes in blood parameters are more commonly observed in ESFT patients with a poor prognosis, 44 a phenomenon that supports the systemic changes of immune cells and cytokines in ESFT patients. Our findings may encourage efforts to target macrophages in ESFT, as currently tested for other types of malignancies using macrophage ablation or restoring their immunostimulatory potential.…”
Section: Discussionmentioning
confidence: 79%
“…42 Tumor-associated macrophages are known to promote cancer cell proliferation, immunosuppression and angiogenesis supporting metastasis and progression and through differentiation to M2 type macrophages expressing anti-inflammatory cytokines (IL-10, TGFβ) that have an inhibitory effect on cytotoxic CD8 + T cells. 43 Interestingly, in the peripheral blood monocytosis and other changes in blood parameters are more commonly observed in ESFT patients with a poor prognosis, 44 a phenomenon that supports the systemic changes of immune cells and cytokines in ESFT patients. Our findings may encourage efforts to target macrophages in ESFT, as currently tested for other types of malignancies using macrophage ablation or restoring their immunostimulatory potential.…”
Section: Discussionmentioning
confidence: 79%
“…Several studies have focused on the identification of micrometastases and CTCs in PB or bone marrow through the detection of EWSR1/FLI1 or EWSR1/ERG fusion transcripts ( Table 3 ). 8 , 22 30 In his study, Dubois describes a novel method of detecting CTCs in patients with ES using flow cytometry with antibodies against CD99 and CD45 to provide an alternative strategy to detect circulating ES tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…This information is mandatory for the identification of therapeutic targets and resistance mechanisms in CTCs, as well as for the stratification of patients and real-time monitoring of systemic therapies. 22 30 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to carcinomas, few studies have investigated the identification of CTCs in sarcomas [ 14 ]. Among mesenchymal tumors, CTCs have been for the most part well-studied in Ewing’s sarcoma/peripheral neuroectodermal tumor (EWS/PNET) [ 15 18 ]. Regarding CTCs in SS, less data is available where investigators have identified the fusion gene product from the peripheral blood of affected patients.…”
Section: Introductionmentioning
confidence: 99%